Shoe dog : a memoir by the creator of Nike - Knight, Philip H., 1938- (London : Simon & Schuster Books for Young Readers, 2017)
"Phil Knight opens up about how he went from being a track star at an Oregon high school to the founder of Nike"--
Young Adult
Young Adult
Keywords: Knight, Philip H., -- 1938- -- Juvenile literature; Knight, Philip H., -- 1938-; Knight, Philip H., -- 1938-; Nike (Firm) -- Juvenile literature; Nike (Firm); Nike (Firm); Businesspeople -- United States -- Biography -- Juvenile literature; Sporting goods industry -- United States -- History -- Juvenile literature; Businesspeople; Sporting goods industry -- History; Businesspeople -- United States -- Biography; JUVENILE NONFICTION / Biography & Autobiography / General; JUVENILE NONFICTION / Business & Economics; JUVENILE NONFICTION / Sports & Recreation / General; Sporting goods industry -- History; Autobiographies